Tinjauan Sosiolinguistik Keigo dalam Manga de Manabu Nihongo Kaiwa Jutsu - Safitri Indah Kurniawati (Japanese Research on Linguistics, Literature, and Culture, 2019)
This paper discusses the use of Japanese keigo respectful types in terms of sociolinguistics. The purpose of this study was to determine the use of Japanese language respect in Nihongo Jaanaru in the Manga de Manabu chapter Nihongo Kaiwa Jutsu. This study uses data sources in the form of Nihongo Jaanaru in the chapter Manga de Manabu Nihongo Kaiwa Jutsu. In this study the discussion of the use of Japanese respect in the Nihongo Jaanaru chapter of the Manga de Manabu Nihongo Kaiwa Jutsu is examined using the distance theory framework proposed by Sachiko's Idea. This distance by Sachiko's idea is used to explain the sociolinguistic aspects of the Japanese respectful variety in Nihongo Jaanaru in the chapter Manga de Manabu Nihongo Kaiwa Jutsu. Based on the findings in the data analysis, the use of keigo is more emphasized on the distance of formality and psychological distance and keigo is used as respect and strategy to achieve the intended purpose.